Methodological review and revision of the Global Hunger Index - Doris Wiesmann; Hans Konrad Biesalski; Klaus von Grebmer; Jill Bernstein (University of Bonn, Center for Development Research (ZEF), 2015)
The Global Hunger Index (GHI) is a multidimensional measure of hunger that considers three dimensions: (1) inadequate dietary energy supply, (2) child undernutrition, and (3) child mortality. The initial version of the index included the following three, equally weighted, non-standardized (i.e. unscaled) indicators that are expressed in percent: the proportion of the population that is calorie deficient (FAO's prevalence of undernourishment); the prevalence of underweight in children under five; and the under-five mortality rate. Several decisions regarding the original formulation of the GHI are reconsidered in light of recent discussions in the nutrition community and suggestions by other researchers, namely the choice of the prevalence of child underweight for the child undernutrition dimension, the use of the under-five mortality rate from all causes for the child mortality dimension, and the decision not to standardize the component indicators prior to aggregation. Based on an exploration of the literature, data availability and comparability across countries, and correlation analyses with indicators of micronutrient deficiencies, the index is revised as follows: (1) The child underweight indicator is replaced with child stunting and child wasting; (2) The weight of one third for the child undernutrition dimension is shared equally between the two new indicators; and (3) The component indicators of the index are standardized prior to aggregation, using fixed thresholds set above the maximum values observed in the data set. The under-five mortality rate from all causes is retained, because estimating under-five mortality attributable to nutritional deficiencies would be very costly and make the production of the GHI dependent on statistics about cause-specific mortality rates by country and year that are published irregularly, while the expected benefits are limited.
Keywords: I13; J13; O15; 330; Global Hunger Index; composite index; food insecurity; child undernutrition; stunting; wasting; underweight; child mortality; micronutrient deficiencies